Optimized Design of Adaptive Headlights for Automobile - Singhal, Ayush; Rawat, Ajay; Tur, Pardeep (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The adaptive headlights use a variable headlight control system geared to the driver’s position on the road. This anticipative illumination of the road ahead is based on a system of sensors. The adaptive headlights direct two headlight modules rotated by motors after sensing steering during the ongoing course of the road, offering the driver a better view at the road ahead both in front and in curves. Adaptive Headlights automatically adjust the light to match the direction of travel. That enables the driver to react more quickly because he/she will see the road ahead more clearly. Sensors monitor steering angles to assure the proper distribution and control of the beam pattern.